2008
DOI: 10.1039/b716317g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolase-catalyzed biotransformations in deep eutectic solvents

Abstract: Hydrolases show good catalytic activity in deep eutectic solvents, despite the presence of urea, which can denature enzymes, or alcohols, which can interfere with hydrolase-catalyzed reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
332
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(355 citation statements)
references
References 30 publications
17
332
0
6
Order By: Relevance
“…Compared to other publications using DES as co-solvent in the biocatalysis, many delightful results exerted on the improvement of reaction rate, not the enantioselectivity. For instance, Gorke et al (2008) reported that the co-solvent DES (ChCl/glycerol) had a great influence on the activity but not on the enantioselectivity in the catalysis of styrene oxide by epoxide hydrolase. Moreover, our previous work also indicated that the addition of DES, ChCl/urea, can improve the catalytic activity of Acetobacter sp.…”
Section: The Effects Of Des Concentration On Epoxide Catalysis By Mehsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other publications using DES as co-solvent in the biocatalysis, many delightful results exerted on the improvement of reaction rate, not the enantioselectivity. For instance, Gorke et al (2008) reported that the co-solvent DES (ChCl/glycerol) had a great influence on the activity but not on the enantioselectivity in the catalysis of styrene oxide by epoxide hydrolase. Moreover, our previous work also indicated that the addition of DES, ChCl/urea, can improve the catalytic activity of Acetobacter sp.…”
Section: The Effects Of Des Concentration On Epoxide Catalysis By Mehsmentioning
confidence: 99%
“…Up to now, DESs have exhibited their application potential because of the advantages of low cost, environmental friendliness, low vapor pressure, low melting point and easy degradation (Flores-Ferrándiz and Chinchilla 2017;Lobo et al 2012a, b). In fact, many reports have shown that deep eutectic solvents can be employed in dissolution and separation (Lu et al 2016;Radošević et al 2016), organic synthesis (Gore et al 2011), electrochemistry (Zhang et al 2012) and catalytic reactions (Cao et al 2016;Gorke et al 2008;Harifi-Mood et al 2017;Xu et al 2015a;Yang and Duan 2016). DESs can be used as not only the co-solvent but also the main reaction medium.…”
Section: Introductionmentioning
confidence: 99%
“…Compare to IL, DES display many advantages such as a low price, a very easy preparation without any purification steps (they are simply prepared by mixing the components), and most of them are biodegradable (Durand, Lecomte, Villeneuve, 2013). Thus, the number of publications dedicated to their use has considerably increased in many fields of research such as metal recovery, gas purification, catalysis, chemical fixation of CO 2 (Li et al, 2008;Su et al, 2009), extraction of phytochemicals from plant material (Dai et al, 2013;Nam et al, 2015) or green solvents for biocatalysis (Alemán et al, 2015;Durand et al,2012;Durand, Lecomte, Baréa, 2013;Gorke et al, 2008;Lindberg et al, 2010;Maugeri et al, 2013;Zhao et al, 2011Zhao et al, , 2013. Recently, the term Natural Deep Eutectic Solvents (NADES) was introduced in literature as a new subfamily of LTTM, to label any mixture combining molecules abundantly present in the cellular constituents (e.g.…”
Section: Lttm a New Family Of Promising Green Mediamentioning
confidence: 99%
“…Gorke et al were the first to use enzymes in DESs and to assess the activity of different hydrolases in choline chloride-urea mixtures. 33 Despite high concentrations of urea, which is a strong hydrogen bond donor and denatures proteins, and the presence of halides, which might inactivate or inhibit the proteins, the enzymes showed good catalytic activity. Furthermore, the conversion of styrene oxide to the corresponding diol with epoxide hydrolase was 20-fold enhanced using choline chloride-urea as a co-solvent (Fig.…”
Section: Biocatalytic Reactionsmentioning
confidence: 99%
“…3). 33 The hydrolysis of epoxides has been studied in more detail by Lindberg et al 80 They investigated the effect of different DESs (1 : 2 mixture of ChCl with urea, ethylene glycol, or glycerol) as co-solvents on the hydrolysis of chiral (1,2)-trans-2-methylstyrene oxide enantiomers by potato EH StEH1 hydrolase. By applying DESs as co-solvents, higher reactant concentrations could be achieved and the regioselectivity could be influenced.…”
Section: Biocatalytic Reactionsmentioning
confidence: 99%